Impact of Different Plant Growth Regulators on Growth, Yield and Quality of Fennel (Foeniculum vulgare Mill.) in Alluvial Regions of West Bengal - Bera, Soumitra; Pariari, Anupam; Singh, Luwangshangbam James; Singha, Utpal (International Journal of Bio-resource and Stress Management, 2024)
An experiment was conducted during the rabi seasons (November, 2018 –April, 2020) at the Horticultural Research Station, Mondouri, Bidhan Chandra Krishi Viswavidyalaya, Mohanpur, Nadia, West Bengal (741 252), India to assess the impact of different plant growth regulators on the growth, yield, and quality of fennel (Foeniculum vulgare Mill.). The experiment was designed in Randomized Block Design with a total of 9 treatment combinations that were replicated three times. Fennel seeds were sown during the first week of November in 2.5×1.5 m2 plots with a spacing of 50×30 cm2. Growth regulators were applied at 30, 45, and 60 days after sowing. The results revealed that the application of naphthalene acetic acid @ 100 ppm significantly optimized fennel yield and quality in the alluvial regions of West Bengal. This was evident through various yield and its attributing parameters, including number of umbel plant-1, number of umbellate umbel-1, number of seeds umbellate-1, test weight (g), and seed yield (22.95 q ha-1) as well as quality parameters including total soluble sugar content (2.91 mg 100 mg-1) and volatile oil content (1.448%). Additionally, Kinetin @ 10 parts per million significantly enhanced the total chlorophyll content (0.344 mg g-1), while gibberellic acid positively influenced growth parameters like plant height, number of primary and secondary branches, days to 50% flowering, flower stalk length, and umbel diameter.